2021
DOI: 10.1038/s41531-021-00250-2
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic factors affecting dopaminergic deterioration during the premotor stage of Parkinson disease

Abstract: To estimate dopaminergic dysfunction in patients with Parkinson disease (PD) during the premotor stage and to investigate the effect of genetic factors on the trajectories. Using longitudinal dopamine transporter single-photon emission computed tomography data from 367 sporadic PD (sPD), 72 LRRK2 (G2019S), and 39 GBA (N370S) PD patients in the Parkinson’s Progression Markers Initiative (PPMI) study, we estimated the temporal trajectories of putaminal-specific binding ratios using an integrating function betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 53 publications
1
11
0
Order By: Relevance
“…Among them, enzymes exist widely in eukaryotes and play an irreplaceable role in defending various tissues and organs against oxidative damage. For instance, GSH can scour free radicals and protect cell membrane and functional integrity; SOD protects the body by scavenging O2- and its level mainly reflects the body’s ability to scavenge oxygen free radicals; MDA mainly reflects the degree of lipid peroxidation in the body [ 42 , 43 , 44 ]. In this work, the activity of GSH and CAT notably down-regulated and the content of MDA clearly increased under cold exposure conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, enzymes exist widely in eukaryotes and play an irreplaceable role in defending various tissues and organs against oxidative damage. For instance, GSH can scour free radicals and protect cell membrane and functional integrity; SOD protects the body by scavenging O2- and its level mainly reflects the body’s ability to scavenge oxygen free radicals; MDA mainly reflects the degree of lipid peroxidation in the body [ 42 , 43 , 44 ]. In this work, the activity of GSH and CAT notably down-regulated and the content of MDA clearly increased under cold exposure conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, the temporal trajectory for putaminal dopaminergic deficit during the premotor period (10 years) in PD patients was modeled using extensive longitudinal PPMI data: according to this model, patients carrying the N370S GBA mutation have more rapid deterioration in dopaminergic function in the premotor phase. 37 In one study, 43 GBA-PD showed a more asymmetric DAT deficit compared to PD patients carrying other mutations with higher penetrance (eg, SNCA). The authors hypothesized that this finding, which resembles what is observed in iPD, suggests that other genetic or environmental factors are needed to drive dopaminergic neuronal loss in GBA-PD.…”
Section: -[ 18 F]fluoro-l-dopa ([ 18 F] Fdopa) Petmentioning
confidence: 97%
“…Greater loss of striatal DAT in the (least-affected) hemisphere ipsilateral to the clinically most affected body side was also demonstrated in a longitudinal PET study using 11C-PE2I, while striatal asymmetry gradually became less prominent despite the persistence of clinical asymmetry [ 14 ]. In addition, integration of DAT decline rate in the putamen using SPECT enables to impute the start of dopaminergic degeneration to around 10 years before motor onset in the Parkinson’s Progression Markers Initiative (PPMI) cohort [ 15 ]. Moreover, DAT-SPECT may be used to improve the prediction of motor progression using machine learning [ 16 , 17 , 18 ], as well as for cognitive outcomes in addition to cerebrospinal fluid (CSF) amyloid and tau [ 19 ].…”
Section: Neurotransmitter Imagingmentioning
confidence: 99%
“…Contrastingly, striatal dopamine synthesis capacity measured with 18F-FDOPA PET in LRRK2 [ 26 ] and heterozygous and homozygous GBA1 mutations carriers without PD [ 29 ] was similar to healthy controls. Interestingly, PD patients with GBA (N370S) mutations may exhibit a faster decline in striatal DAT availability during the premotor phase compared to patients with LRRK2 mutation or idiopathic PD using DAT SPECT in the PPMI cohort [ 15 ], while 18-FDOPA rate of change in GBA1 mutation carriers was similar to controls [ 29 ]. Moreover, a steady decline of DAT was previously reported in asymptomatic LRRK2 G2019S mutation carriers, comparable to the rate in patients converting to PD, which was determined by lower baseline striatal DAT availability [ 30 , 31 ].…”
Section: Neurotransmitter Imagingmentioning
confidence: 99%
See 1 more Smart Citation